Effect of Study Duration and Outcome Measurement Frequency on Estimates of Change for Longitudinal Cohort Studies in Routinely-Collected Administrative Data - Feely, Allison; Wall-Wieler, Elizabeth; Roos, Leslie L; Lix, Lisa (International Journal of Population Data Science, 2020)
Introduction: When designing prospective and retrospective longitudinal cohort studies, investigators must make decisions about study duration (i.e. length of follow-up) and frequency of outcome measurement. The impact of these decisions have been previously investigated in the prospective setting, but have not been described for retrospective cohort studies. Objectives: To examine the impact and potential challenges of longitudinal design decisions in retrospective cohort studies and illustrate the effects of varying study duration and frequency of outcome measurement in the retrospective setting using a numeric example. Methods: Linked administrative data from Manitoba was used. The cohort included all mothers who experienced the death of an infant between April 1, 1999 and March 31, 2012 and a matched (3:1) group of mothers who did not experience death. A generalized linear mixed model was used to model differences in the trend in the number of healthcare contacts for the two groups. Holding sample size constant, the model was fit to the data for combinations of duration and frequency. Estimated standard errors and regression coefficients were compared. Results: A total of 2576 mothers were included; 644 experienced death of an infant and 1932 were matched to this group. Thirteen combinations of frequency (1, 2, 3, 4 periods/year) and duration (1, 2, 3, 4 years) were compared. As frequency increased from 1 to 4 periods/year, the standard error of the group-time-time interaction decreased up to 98.9%. As duration increased from 1 to 4 years, the standard error of the interaction decreased up to 96.9%. As frequency and duration increased, the coefficients trended toward zero. Conclusions: Retrospective designs using administrative data offer greater flexibility to select time-related design elements than prospective designs, but present potential new challenges. Recommendations about how to select and report time-related design decisions in retrospective cohort studies should be included in reporting guidelines.